If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(m + -2) + -2 = 3(m + -4) Reorder the terms: 2(-2 + m) + -2 = 3(m + -4) (-2 * 2 + m * 2) + -2 = 3(m + -4) (-4 + 2m) + -2 = 3(m + -4) Reorder the terms: -4 + -2 + 2m = 3(m + -4) Combine like terms: -4 + -2 = -6 -6 + 2m = 3(m + -4) Reorder the terms: -6 + 2m = 3(-4 + m) -6 + 2m = (-4 * 3 + m * 3) -6 + 2m = (-12 + 3m) Solving -6 + 2m = -12 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. -6 + 2m + -3m = -12 + 3m + -3m Combine like terms: 2m + -3m = -1m -6 + -1m = -12 + 3m + -3m Combine like terms: 3m + -3m = 0 -6 + -1m = -12 + 0 -6 + -1m = -12 Add '6' to each side of the equation. -6 + 6 + -1m = -12 + 6 Combine like terms: -6 + 6 = 0 0 + -1m = -12 + 6 -1m = -12 + 6 Combine like terms: -12 + 6 = -6 -1m = -6 Divide each side by '-1'. m = 6 Simplifying m = 6
| pir^2=0 | | (x-50)= | | 300x-0.03=500x+0.55 | | I=113x-225602 | | q^4+29p^2+100=0 | | (130-x)= | | 15x+3=15x-3 | | 17x^2-2x=6x-31x^2 | | 16-2n-5n+8n=65 | | (x+21)= | | 2f-9=27-f | | 70=2/1/2t | | 70=21/2t | | 10y+9=2y+10 | | 8/35x13 | | -3x+8=-7x | | (x+62)= | | 3(6)+2y=-6 | | 25m+10m^2= | | 1/10x=1/14-8/15 | | 3x+7=7(x+1)-4x | | |7/10| | | y-6=-6x(x+4) | | -2x+60=4x-20 | | H=-16t^2+45t+2.5 | | 0.8(x+70)+0.2x=81 | | (2x-7)= | | 4x+4=2-(3x-6) | | X^2+x-12=o | | 4x+1.20=7.20 | | 3(5)+2y=-6 | | 2(x-1)-3=7 |